Multi-Scale Pore Structure Characterization of Silurian Marine Shale and Its Coupling Relationship With Material Composition: A Case Study in the Northern Guizhou Area - Du, Wei; Lin, Ruiqin; Shi, Fulun; Luo, Nina; Wang, Yisong; Fan, Qingqing; Cai, Junying; Zhang, Ziya; Liu, Li; Yin, Wei; Zhao, Fuping; Sun, Zhao; et al. (Frontiers in Earth Science, 2022)
Investigation of pore structure is vital for shale reservoir evaluation and also “sweet spot” prediction. As the strong heterogeneity in pore types, morphology and size distributions of organic matter-rich shales, it is essential to combine different approaches to comprehensively characterize them. field emission-scanning electron microscopy, low-pressure gas adsorption and high pressure mercury intrusion were employed to systematically investigate the pore structure of the lower Longmaxi shale reservoirs in the northern Guizhou area. The results show that, the shales can be divided into four lithofacies based on minerals composition, namely, siliceous shale (SS), clay shale (CS), carbonate shale (CAS) and mixed shale (MS), among which siliceous shale is the primary lithofacies of the Longmaxi shale. Numerous organic matter (OM)-hosted pores, clay interlayer pores, interparticle pores and intraparticle pores were identified within shale reservoirs. The specific surface area ranges from 11.3 m2/g to 27.4 m2/g, with an average of 18.1 m2/g. It exhibits a strong positive correlation with TOC contents, suggesting that organic matter is the major contributor to the specific surface areas. A wide range of pore size distribution was measured by integration of gas adsorption and HPMI. It is shown that the pore size is primarily distributed within ~100 nm, corresponding to micropores, mesopores and part of macropores. The total pore volume, which is mostly derived from the contribution of micropores and mesopores, remains within a range of between 0.11 ml/g to 0.025 ml/g, with an average of 0.018 ml/g. Furthermore, the volume of micropores and mesopores is mainly controlled by organic matter contents. The dissolution pore contributes most to the macropore space within shale reservoirs, based on the positive correlation with macropore volume and easily dissolved minerals, including carbonate and feldspar. What’s more, the total pores volume is mainly dominated by organic matter and carbonate contents. This is possibly attributed to the easily dissolved and rigid features of carbonate, which can protect the primary interparticle pores due to its high compression resistance and is conducive to forming abundant dissolution pores. OM-rich carbonate bearing mixed shale may be the most favorable lithofacies for gas storage in the northern Guizhou area.